The Emergence of Large Shareholders in Mass Privatized Firms: Evidence from Poland and the Czech Republic - Irena Grosfeld; Iraj Hashi (Fondazione Eni Enrico Mattei (FEEM), 2004)
Mass privatization offers a particularly suitable framework to study the change in ownership concentration as the extent of change is unusual for a stable market economy. Focusing on two different mass privatization schemes in two transition economies, Poland and the Czech Republic, we find that despite important differences in the design of the two programmes and despite different quality of legal and regulatory framework, ownership structure in the two countries has rapidly evolved and the emerging ownership patterns are remarkably similar. This suggests that private benefits of control are large and the quality of investor protection regime is low in both countries. However, looking at the relationship between the change in ownership concentration and firm performance, we find an interesting difference between the two countries: in the Czech Republic the increase in ownership concentration seems to be less likely in poorly performing firms while in Poland the quality of past performance does not affect investors' willingness to increase their holdings. This effect may be interpreted in the light of the theory stressing the importance of the quality of investors' protection. It could be argued that if Czech investors are more risk averse and more concerned with diversification this is largely due to the weakness of the legal protection they face.
Keywords: G3; L2; P3; P5; 330; Ownership concentration; Mass privatisation; Corporate governance; Transition; Eigentümerstruktur; Privatisierung; Corporate Governance; Polen; Tschechien